Third Way, Third Sector and the partnership IAS/public education system in Brazil - Vera Maria Vidal Peroni; Josiane Carolina Soares Ramos do Amaral; Luciani Paz Comerlatto; Marilda de Oliveira Costa; Maria Otilia Kroeff Susin (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
This paper aims to debate on the public-private partnerships in education and to bring elements from the third way and third sector as an important part of this topic. And to present some consequences of the partnerships for democratic management, that is, how the logic of market as a parameter of efficiency is incorporated by public administration, and the consequences of this fact on the educational policies.